Isolation, Identification and Quantitative Determination of Anthracene Derivatives by HPLC-UV Method in the Raw Materials of Some Representatives of the Genus Rumex of Three Vegetation Times - A. M. Poluyanov; A. Yu. Sokolova; E. A. Malashenko; E. V. Sergunova; N. V. Bobkova (Разработка и регистрация лекарственных средств, 2022)
Introduction. The creation of new highly effective drugs requires a thorough study of the metabolome of plant raw materials and a comparative phytochemical study of the underground organs of closely related species of Rumex, such as: R. crispus, R. obtusifolius and R. aquaticus, ubiquitous in Russia. It was noted that they have a metabolome like the official R. confertus, which in turn confirms the potential for studying these species. Of scientific and practical interest is the study of the dynamics of accumulation of the leading group of biologically active substances – anthracene derivatives, depending on the phenological phases of plant development.Aim. Identify and quantify anthracene derivatives in the underground organs of R. confertus, R. crispus, R. obtusifolius and R. aquaticus harvested in three different phases of vegetation.Materials and methods. Extracts from the underground organs of the studied plants obtained according to the method from the pharmacopoeial article on R. confertus were used as the analyzed solutions. The solutions were analyzed on a Nexera-i LC-2040 chromatograph (Shimadzu Corporation, Japan) equipped with a column and sample thermostat, a degasser, and an autosampler using an individually selected mobile phase elution gradient (0.1 % phosphoric acid/acetonitrile solution). Primary data were processed using LabSolutions Single LC software (Shimadzu Corporation, Japan). Compounds from the group of anthracene derivatives were identified by retention times. Detection was carried out using a UV detector with a dynamic change in the absorption wavelength during analysis from 365 ± 2 nm to 254 ± 2 nm.Results and discussion. Alcohol-water extracts were obtained from the underground organs of Rumex. An elution gradient was selected for the simultaneous determination of 5 anthracene derivatives with a single analysis time of 40 minutes. These chromatographic conditions made it possible to identify and quantify the content of emodin, 8-O-β-D-glucoside of emodin, and chrysophanol in the underground organs of R. confertus, R. crispus, R. obtusifolius and R. aquaticus in three different vegetations. Glycosides of anthracene derivatives: glucofrangulin A and frangulin A were not found in the studied objects.Conclusion. Anthracene derivatives were isolated from the underground organs of different vegetations, a method for the quantitative determination of anthracene derivatives in alcohol-water extracts was developed, emodin, 8-O-β-D-glucoside of emodin and chrysophanol were found and quantified.